COMPARISON OF THE CHAIN LADDER AND BORNHOUTTER-FERGUSON METHODS IN CALCULATING CLAIM RESERVES FOR REINSURANCE COMPANY IN INDONESIA - Yulita, Tiara; Julianty, Dila Tirta; Aprilia, Inaya Sathrani; Inayah, Larasati Nurul (VARIANCE: Journal of Statistics and Its Applications, 2025)
In the insurance industry, calculating claims reserves plays a crucial role in managing both risk and the financial stability of an insurance company. When a claim is filed, the insurer must allocate a reserve fund to anticipate potential future losses. In general insurance, claim settlements are often not completed immediately because there is usually a time gap between the occurrence of an incident and the reporting of the claim. Unresolved claims create liabilities or obligations for the insurance company. These allocated funds are referred to as claim reserves, which are generally categorized into two types: Incurred but Not Reported (IBNR) and Reported but Not Settled (RBNS). This research focuses on determining estimates of claim reserves using the Chain Ladder and Bornhuetter-Ferguson methods for loss insurance data for the property business class of reinsurance companies in Indonesia for the period 2011 to 2021. The results show that the claims reserves for each method are IDR 2,499,456,710,993 and IDR 2,266,000,657,647 with MAPE value of 1.38% and 2.10%. The results of the MAPE value calculation show that the claim reserves estimate using the Chain Ladder method is better than the Bornhuetter-Ferguson method.